A miRNA biosensor based on localized surface plasmon resonance enhanced by surface-bound hybridization chain reaction - Miti, Andrea (Biosens Bioelectron, 2020)
The dysregulation of the concentration of individual circulating microRNAs or small sets of them has been recognized as a marker of disease. For example, an increase of the concentration of circulating miR-17 has been linked to lung cancer and metastatic breast cancer, while its decrease has been found in multiple sclerosis and gastric cancer. Consequently, techniques for the fast, specific and simple quantitation of microRNAs are becoming crucial enablers of early diagnosis and therapeutic follow-up. DNA based biosensors can serve this purpose, overcoming some of the drawbacks of conventional lab-based techniques. Herein, we report a cost-effective, simple and robust biosensor based on localized surface plasmon resonance and hybridization chain reaction. Immobilized gold nanoparticles are used for the detection of miR-17. Specificity of the detection was achieved by the use of hairpin surface-tethered probes and the hybridization chain reaction was used to amplify the detection signal and thus extend the dynamic range of the quantitation. Less than 1 h is needed for the entire procedure that achieved a limit of detection of about 1 pM or 50 amol/measurement, well within the reported useful range for diagnostic applications. We suggest that this technology could be a promising substitute of traditional lab-based techniques for the detection and quantification of miRNAs after these are extracted from diagnostic specimens and their analysis is thus made possible.